Vascular smooth muscle cell death, autophagy and senescence in atherosclerosis. Issue 4 (18th January 2018) - Grootaert, Mandy O J; Moulis, Manon; Roth, Lynn; Martinet, Wim; Vindis, Cécile; Bennett, Martin R; De Meyer, Guido R Y
Abstract: In the present review, we describe the causes and consequences of loss of vascular smooth muscle cells (VSMCs) or their function in advanced atherosclerotic plaques and discuss possible mechanisms such as cell death or senescence, and induction of autophagy to promote cell survival. We also highlight the potential use of pharmacological modulators of these processes to limit plaque progression and/or improve plaque stability. VSMCs play a pivotal role in atherogenesis. Loss of VSMCs via initiation of cell death leads to fibrous cap thinning and promotes necrotic core formation and calcification. VSMC apoptosis is induced by pro-inflammatory cytokines, oxidized low density lipoprotein, high levels of nitric oxide and mechanical injury. Apoptotic VSMCs are characterized by a thickened basal lamina surrounding the cytoplasmic remnants of the VSMC. Inefficient clearance of apoptotic VSMCs results in secondary necrosis and subsequent inflammation. A critical determinant in the VSMC stress response and phenotypic switching is autophagy, which is activated by various stimuli, including reactive oxygen and lipid species, cytokines, growth factors and metabolic stress. Successful autophagy stimulates VSMC survival, whereas reduced autophagy promotes age-related changes in the vasculature. Recently, an interesting link between autophagy and VSMC senescence has been uncovered. Defective VSMC autophagy accelerates not only the development of stress-induced premature senescence but also atherogenesis, albeit without worsening plaque stability. VSMC senescence in atherosclerosis is likely a result of replicative senescence and/or stress-induced premature senescence in response to DNA damaging and/or oxidative stress-inducing stimuli. The finding that VSMC senescence can promote atherosclerosis further illustrates that normal, adequate VSMC function is crucial in protecting the vessel wall against atherosclerosis.